A study on "Kuwaitization" of private sector initiatives (2012-2016) - Saeid, Muna H. (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This thesis discussed the initiatives of “Kuwaitization” in the private sector and the reasons of the failure of these initiatives. The public sector in Kuwait lacked a huge number of Kuwaiti employees. In contrast, the private sector focuses exclusively on expatriate employees. Such a problem might be risky due to the demographic structure and affects the economy of Kuwait as all the money and salaries paid to expatriates are transferred abroad, which might cause a complicated economic situation for Kuwait. It mainly discussed the important challenges faced Kuwaiti government in its attempts to settle jobs for Kuwaitis in the private sector. It also highlights the reasons for the reluctance of Kuwaiti youth to work in the private sector. The thesis mentioned some socio-cultural, institutional, political and economic factors along with the current practices of the government and the impact of these factors on the “Kuwaitization” process in the private sector. Human resource managers in the private sectors in Kuwait are involved in this thesis to seek efficient answers for the reasons of reluctance of Kuwaitis to work in the private sector and to determine the criteria they use to choose employees in their companies. In this thesis, many tools and methods were used to examine the model of the study. In order to suggest solutions that could contribute to the model used, 491 of Kuwaiti employees answered a survey and 19 of Human Resource managers in the private sectors were approached with interviews.